Application of SMART Method in Insurance Selection Decision Support System - Ade Dwi Satya (International Journal of Basic and Applied Science, 2021)
The background of making the system is that there are still many people who still think that insurance is not useful due to their lack of understanding of the need for proper insurance. The purpose of making this system is to make it easier for people who want to register as insurance policy holders or just to get information on what type of insurance is suitable for them. The making of this system is based on data obtained from the Yogyakarta branch of the Prudential company which is then used as the basis for calculating the system using the SMART (Simple Multi Attribute Rating Technique) method. the calculation of the questionnaire which reached 77